Willingness to Communicate (WTC) among Intermediate-level Adult Turkish EFL Learners: Underlying Factors - Fatma Aydın (Anı Publishing, 2017)
The present qualitative study investigates the underlying factors of willingness to communicate (WTC) among intermediate-level adult Turkish EFL learners studying at the school of foreign languages of Anadolu University. WTC is defined as "a readiness to enter into discourse at a particular time with a specific person or persons, using a L2" (MacIntyre, Clement, Dörnyei and Noels, 1998: 547). In the current study, WTC refers to a more general willingness to participate in English lesson, communicate in English both verbally and in a written way and accordingly learn English. The participants are five students who are believed to have varying levels of WTC according to their teacher's observation. They were told the purpose of the study and what is exactly meant by WTC. The qualitative data were collected using an open-ended questionnaire, two sessions of semi-structured interviews and six journal entries per participant. The data were analyzed using thematic analysis. Once the codes and themes were constructed and as a result the factors affecting the participants' WTC behavior in a foreign language classroom were found, quotations were provided to support the findings. Finally, implications for teachers and administrators and suggestions for further research were propounded.